An overview of offender profiling - Kapardēs, Andreas (International journal of police science & management, 2024)
Generally speaking, criminals are caught by police for one or more of the following reasons: they confess to the crime; another criminal gives the police useful information about a crime; they are arrested red-handed or chased and caught by police; an eyewitness describes them; forensic evidence (fingerprints, footprints, DNA, etc.) at the crime scene or their handwriting or video footage is linked to them; or finally, because the police link a number of crimes committed by the same offender. Further, in today's large urban centres all over the world, the work of police detectives is becoming increasingly difficult, calling for more sophisticated techniques as criminals become even more adept. Films such as Silence of the Lambs, television series like Cracker in the UK, Mindhunter, CSI: Crime Scene Investigation, CSI: Miami or Profiler, and popular books like The Real Cracker by Stephen Cook (2001), The Jigsaw Man and Picking Up the Pieces by Paul Britton (1998, 2001) have popularised criminal profiling. In addition, well-known retired Federal Bureau of Investigation profilers (e.g. John Douglas, Roy Hazelwood, Robert Ressler) have published some of their experiences in helping law enforcement agencies catch serial killers. Likewise, in the UK, two very experienced offender profilers have published works; namely, academic psychologist Julian Boon and psychiatrist Richard Baddock. Offender profiling refers to the use of behavioural data evident in a crime to assist a police investigation by seeking to infer attributes of probable offenders, thus narrowing the police search for suspects.